APPLICATION OF ADVANCED STATISTICAL SOFTWARE IN RESEARCH AND EDUCATION - Глушко, Аліна; Токар, Олександр (SWorldJournal, 2025)
The purpose of this article is to analyze the potential of modern software tools to enhance the quality of statistical research. In light of the growing volume of data and the increasing demand for its rapid processing, the application of advanced statist